If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 6x + 3 = 12 Reorder the terms: 3 + 3x + 6x = 12 Combine like terms: 3x + 6x = 9x 3 + 9x = 12 Solving 3 + 9x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 9x = 12 + -3 Combine like terms: 3 + -3 = 0 0 + 9x = 12 + -3 9x = 12 + -3 Combine like terms: 12 + -3 = 9 9x = 9 Divide each side by '9'. x = 1 Simplifying x = 1
| 7x+1x=48 | | 5x/2=30 | | 5x/8=20 | | 2(X.+.140)=920 | | 3x+18/7-2x=18/35 | | -4t^2+13t+7=0 | | 776=x+x+25+x-29-2x | | 776=x+x+25(29-2x) | | 776=x+x+25+(29-2x) | | 12x^2-9x-4=0 | | 4x-(x-1)=22 | | 776=x+x+25+29-2x | | a^3/2/3a^3 | | 6n+2(2n-8)= | | (6x/y^2)*(9y/5x) | | 9x-13=5x+4 | | 2(3x-1)=21 | | 2(1/8)+1/3 | | (x-3)(3x+5)+4x(2x+1)=7x^2+12x-20 | | 12x+8=77x+33 | | 12/40 | | 8s-8=-5+9s | | x-0.6=8.36 | | -35y=175 | | (10x^6/y^8)*(6/2x^6y^8) | | 154/60 | | 5x^4+4=324 | | 2(x^3)+11(x^2)-7x-6=0 | | x/3=x-8 | | (5x/y^2)*(7y/6x) | | st+s-3=5-3 | | 8/0.5/0.5/(-2)+8*0.5 |